Establishing Collaboration Practice in an English Young Learner Classroom - Suci Din Awdilah Nur; Pratiwi, Diwani (International Journal of Contemporary Studies in Education, 2024)
Collaborative Learning is an educational approach to teaching and learning that involves groups of learners working together to solve a problem, complete a task. it is not easy for a teacher to apply collaboration to young learner students in the classroom, it could be that a young learner’s emotions are still unstable, students are selfish who tend to like to do their own work and feel annoyed because they have to work with their friends who may be a little lacking and finally these superior students feel worried about their grades if they are directed to work with students who are slightly lacking in knowledge This paper aims to discuss the strategies that a teacher can use in deepening collaboration between students in the classroom.